Teaching Media -- Medientheorie für die Schulpraxis - Grundlagen, Beispiele, Perspektiven (unter Mitarbeit von Linda Leskau, Kathrin Lohse, Arne Malmsheimer und Jens Schröter) - Kampmann, Elisabeth (Pädagogik, 2017)
Nowadays, media determine the daily routine of schools. But what are media? How has media been fought about over the centuries? This volume offers the foundations for a qualified confrontation with questions of media reflection and the use of media in school praxis. A historical overview shows the structures of the debates around the possibilities and dangers of the use of media, and thus serves to make the debate more objective. The comprehensible and competent representation of the central concepts, developments and discoveries of media theory make this book essential reading for students in education and student teachers from diverse subject areas.